IMPLEMENTASI MODEL PEMBELAJARAN GUIDED INQUIRY PADA MATA PELAJARAN ILMU UKUR TANAH - Aini Tazkiyah (Jurnal Salome : Multidisipliner Keilmuan, 2024)
Implementation of the Guided Inquiry Learning Model in Ilmu Ukur Tanah" aims to improve students understanding and skills in understanding important concepts in Ilmu Ukur Tanah. Guided Inquiry is a learning approach that encourages students to be active in constructing their knowledge through a process of inquiry and exploration. In the context of geometry, this model allows students to be actively involved in measurement, data analysis, and problem- solving. In this implementation, the teacher acts as a facilitator who supports students in carrying out their investigations. Students are encouraged to ask questions, plan experiments, collect data, and draw conclusions based on their findings. This not only improves understanding of concepts but also develops critical thinking skills and collaborative abilities. The research results show that the implementation of the Guided Inquiry Model is effective in improving student learning achievement in Ilmu Ukur Tanah. Students demonstrate improvements in their understanding of key concepts as well as their ability to apply that knowledge in relevant contexts. Apart from that, students also experienced increased motivation and interest in learning land surveying. Thus, the implementation of the Guided Inquiry Model in Ilmu Ukur Tanah can be used as an effective learning strategy to improve students understanding of concepts and skills. This approach not only promotes active and collaborative learning but also helps students develop skills that are relevant to the real world.